Growth and Yield of Green Eggplant Applied to Various Compositions of Growing Media - Sheila Izdihar Hendra Putri; Maria Fitriana (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
Green eggplant was a vegetable which used for cooking ingredients and has rich nutrients. To increase the green eggplant productivity, it was necessary to improve the quality of growing media so the plant nutrition will be fulfilled. This study aimed to find out the best composition of growing media for the growth and yield of green eggplant. It used a Randomized Block Design (RBD) with 10 treatments for the composition of the growing media. The results of the analysis of diversity showed that the application of rice husk charcoal and chicken manure had a very significant effect on plant height, number of leaves, stem diameter, flowering age, harvest age, number of fruits per plant, fruit length, fruit diameter, and total fruit weight per plant. The results of the orthogonal contrast test showed that the green eggplant grown on soil media was very significantly different from the green eggplant grown on other growing media in all variables. The best results were obtained from the treatment of rice husk charcoal: chicken manure: soil (2:1:1) on the variables of plant height was 42.26 cm, flowering age was 22.33 days, total fruit weight per plant was 538.44 g, fruit diameter was 38.16 mm, and average weight per fruit was 81.66 g. The treatment of growing media composition using a combination of chicken manure and rice husk charcoal was better than the growing media with just one organic matter.